Mice Deficient in Nucleoporin Nup210 Develop Peripheral T Cell Alterations - van Nieuwenhuijze, Annemarie; Burton, Oliver; Lemaitre, Pierre; Denton, Alice E.; Cascalho, Ana; Goodchild, Rose E.; Malengier-Devlies, Bert; Cauwe, Bénédicte; Linterman, Michelle A.; Humblet-Baron, Stephanie; Liston, Adrian (Frontiers in Immunology, 2018)
The nucleopore is an essential structure of the eukaryotic cell, regulating passage between the nucleus and cytoplasm. While individual functions of core nucleopore proteins have been identified, the role of other components, such as Nup210, are poorly defined. Here, through the use of an unbiased ENU mutagenesis screen for mutations effecting the peripheral T cell compartment, we identified a Nup210 mutation in a mouse strain with altered CD4 / CD8 T cell ratios. Through the generation of Nup210 knockout mice we identified Nup210 as having a T cell-intrinsic function in the peripheral homeostasis of T cells. Remarkably, despite the deep evolutionary conservation of this key nucleopore complex member, no other major phenotypes developed, with viable and healthy knockout mice. These results identify Nup210 as an important nucleopore complex component for peripheral T cells, and raise further questions of why this nucleopore component shows deep evolutionary conservation despite seemingly redundant functions in most cell types.